Risk factors for post-induction hypotension in patients with end-stage renal disease undergoing general anesthesia - Supachai Trikisayaveach; Laortip Rattanapittayaporn; Jatuporn Pakpirom; Chutida Sungworawongpana; Suttasinee Petsakul (PLoS ONE, 2026)
Background Patients with end-stage renal disease (ESRD) are at highly susceptible to hemodynamic instability during anesthesia induction. However, data specific to this population remain limited. Methods This retrospective cohort study included 635 adult patients with ESRD who underwent non-cardiac surgery under general anesthesia between 2012 and 2022. Post-induction hypotension was defined as a ≥ 30% reduction in mean arterial pressure (MAP) from baseline within 20 minutes after induction, requiring vasopressor support. Multivariable logistic regression was performed to identify independent predictors. Results The incidence of post-induction hypotension was 44.1% (95% confidence interval (CI), 40.2–47.9). Independent predictors included age > 65 years, chronic oral antidiabetic therapy, higher propofol dose, rapid sequence induction, and emergency surgery. The incidence of hypotension peaked at 20 min after induction. Dialysis-related variables were not significantly associated with hypotension. Conclusion Post-induction hypotension is common in patients with ESRD and associated with advanced age, chronic antidiabetic therapy, higher propofol dose, rapid sequence induction, and emergency surgery.